2018
DOI: 10.1111/ejn.14217
|View full text |Cite
|
Sign up to set email alerts
|

The role of the dorsolateral prefrontal cortex in the motor placebo effect

Abstract: The neural correlates of the placebo effect in the motor domain are still unknown. The aim of this study was to tackle the role of a frontal cortical region, the dorsolateral prefrontal cortex (dlPFC). To this end, we stimulated the cortical site corresponding to the left dlPFC with transcranial direct current stimulation (tDCS) during a placebo procedure and measured any change in the motor placebo effect in all the participants and more specifically in placebo‐responders. Three different experiments were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 84 publications
(130 reference statements)
0
11
0
Order By: Relevance
“…This improvement was also retained in 48-h retention tests suggesting positive and lasting neurophysiological impact [ 18 ]. Moreover, recent findings suggest that tDCS applied to the PFC may actually nullify placebo-induced enhancement of motor force [ 59 ]. Dampening down of motor placebo effects through our stimulation protocol provides further evidence to support the validity of the increased KTS being attributable to the application of active tDCS.…”
Section: Discussionmentioning
confidence: 99%
“…This improvement was also retained in 48-h retention tests suggesting positive and lasting neurophysiological impact [ 18 ]. Moreover, recent findings suggest that tDCS applied to the PFC may actually nullify placebo-induced enhancement of motor force [ 59 ]. Dampening down of motor placebo effects through our stimulation protocol provides further evidence to support the validity of the increased KTS being attributable to the application of active tDCS.…”
Section: Discussionmentioning
confidence: 99%
“…Emergent studies have suggested a mechanical and neurophysiological mechanism (peripheral, spinal and supraspinal) as the base of the effects induced by the therapeutic interventions adopted by the physiotherapists [35][36][37]. Considering the supraspinal mechanisms, placebo and nocebo effects were indicated as important top-down modulators of patient's symptoms, mainly pain and motor performance [38][39][40][41][42][43][44], thus becoming elements that physiotherapists should attentively consider in their clinical practice [17].…”
Section: Introductionmentioning
confidence: 99%
“…Using this framework, it is reasonable to hypothesize that subjective expectations could induce a particular brain state that in turn interacts with the effect of the magnetic or electrical stimulation. With respect to this, it is well established that the dorsolateral prefrontal cortex (dlPFC) is involved in elaborating expectations [ 48 , 125 ] and plays a prominent role, together with other brain regions, in the placebo effect [ 48 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ]. Moreover, this associative brain area is involved in many higher-order cognitive functions, such as working memory [ 134 , 135 ], strategic planning ability [ 136 ], and attention [ 137 ], and plays a significant role in the executive top-down control of behavior [ 138 ].…”
Section: Discussionmentioning
confidence: 99%